Fast-paced and violent media exposure are positively associated with ADHD and impulsivity in college students - Hayes, Nicole L.; Anderson, Craig A.; Swing, Edward L. (Frontiers in Psychology, 2025)
IntroductionPrevious research reveals that screen media exposure is positively associated with attention problems and impulsivity.MethodsThree cross-sectional correlational studies examined the extent to which fast-paced versus violent media exposure are associated with attention-related problems in college students. Multiverse data analyses tested the robustness of results. Fast-paced and violent media effects were examined separately and uniquely using SEM.ResultsA Pilot study (N = 233) found weak but significant zero-order correlations of both fast-paced and violent media exposure on self-control. However, the main SEM results were not significant, although in the expected direction, perhaps because of single-item assessments of media pacing and violence. Main Studies 1 (N = 438) and 2 (N = 456) found that exposure to fast-paced media was positively associated with ADHD-symptoms; this effect was reduced when media violence was added to the model. Both studies also found that greater exposure to violent content was uniquely and positively associated with impulsivity.DiscussionOverall, findings suggest that fast-paced and violent media yield small but reliable effects that may play an important role in attention-related problems in young adults. Future research should continue to investigate the relationships between media use on attention-related problems, especially longitudinal studies to test direction of causality.